Gadolinium is not necessary for surveillance MR imaging in children with chiasmatic‐hypothalamic low‐grade glioma. Issue 10 (16th June 2021) - Malbari, Fatema; Chintagumpala, Murali M.; Wood, Alexis C.; Levy, Adam S.; Su, Jack M.; Okcu, M. Fatih; Lin, Frank Y.; Lindsay, Holly; Rednam, Surya P.; Baxter, Patricia A.; Paulino, Arnold C.; Orzaiz, Guillermo Aldave; et al.
Abstract: Background: Patients with chiasmatic‐hypothalamic low‐grade glioma (CHLGG) have frequent MRIs with gadolinium‐based contrast agents (GBCA) for disease monitoring. Cumulative gadolinium deposition in the brains of children is a potential concern. The purpose of this study is to evaluate whether MRI with GBCA is necessary for determining radiographic tumor progression in children with CHLGG. Methods: Children who were treated for progressive CHLGG from 2005 to 2019 at Texas Children's Cancer Center were identified. Pre‐ and post‐contrast MRI sequences were separately reviewed by one neuroradiologist who was blinded to the clinical course. Three dimensional measurements and tumor characteristics were evaluated. Radiographic progression was defined as a 25% increase in size (product of two largest dimensions) compared with baseline or best response after initiation of therapy. Results: A total of 28 patients with progressive CHLGG were identified with a total of 683 MRIs with GBCA reviewed (mean 24 MRIs/patient; range, 11‐43 MRIs). Radiographic progression was observed 92 times, 91 (99%) on noncontrast and 90 (98%) on contrast imaging. Sixty‐seven progressions necessitating management changes were identified in all (100%) noncontrast sequences and 66 (99%) contrast sequences. Tumor growth > 2 mm in any dimension was identified in 184/187 (98%) noncontrast and 181/187 (97%) with contrast imaging. Metastatic tumors were better visualized on contrast imaging in 4/7 (57%). Conclusion: MRI without GBCA effectively identifies patients with progressive disease. When imaging children with CHLGG, eliminating GBCA should be considered unless monitoring patients with metastatic disease.